Global, regional and national availability of essential medicines for children, 2009-2020: a systematic review and meta-analysis - Yuqing Shi; Zhe Chen; Kun Zou; Miao Zhang; Zheng Liu; Dan Liu; Linan Zeng; Hailong Li; Zhi-Jun Jia; Guo Cheng; Yong Tang; Shaoyang Zhao; et al. (BMC, 2023)
Abstract Background Access to essential medicines is a vital component of universal health coverage. The low availability of essential medicines for children (EMC) has led the World Health Organization (WHO) to issue a number of resolutions calling on member states on its improvement. But its global progress has been unclear. We aimed to systematically evaluate the progress of availability of EMC over the past decade across economic regions and countries. Methods We searched eight databases from inception to December 2021 and reference lists to identify included studies. Two reviewers independently conducted literature screening, data extraction and quality evaluation. This study was registered with PROSPERO, CRD42022314003. Results Overall, 22 cross-sectional studies covering 17 countries, 4 income groups were included. Globally, the average availability rates of EMC were 39.0% (95%CI: 35.5-42.5%) in 2009-2015 and 43.1% (95%CI: 40.1-46.2%) in 2016-2020. Based on the World Bank classification of economic regions, income was not proportional to availability. Nationally, the availability rate of EMC was reasonable and high (> 50%) in only 4 countries, and low or very low for the rest 13 countries. The availability rates of EMC in primary healthcare centers had increased, while that for other levels of hospitals slightly declined. The availability of original medicines decreased while that of generic medicines was stable. All drug categories had not achieved the high availability rate. Conclusion The availability rate of EMC was low globally, with slight increase in the last decade. Continuous monitoring and timely reporting of the availability of EMC are also needed to facilitate targets setting and inform relevant policy making.